2020
DOI: 10.1101/2020.02.04.933911
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell Atlas of Aqueous Humor Outflow Pathways in Eyes of Humans and Four Model Species Provides Insights into Glaucoma Pathogenesis

Abstract: ABSTRACTIncreased intraocular pressure (IOP) represents a major risk factor for glaucoma, a prevalent eye disease characterized by death of retinal ganglion cells that carry information from the eye to the brain; lowering IOP is the only proven treatment strategy to delay disease progression. The main determinant of IOP is the equilibrium between production and drainage of aqueous humor, with compromised drainage generally viewed as the primary contributor to dangerous IOP elev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…S3). Indeed, in a parallel study, we have demonstrated expression of these genes in cells of the aqueous humor outflow pathways 53 .…”
Section: Expression Of Genes Implicated In Retinal Diseasementioning
confidence: 85%
“…S3). Indeed, in a parallel study, we have demonstrated expression of these genes in cells of the aqueous humor outflow pathways 53 .…”
Section: Expression Of Genes Implicated In Retinal Diseasementioning
confidence: 85%
“…Not only could we identify cell types of the cornea and AL, but we were also able to follow clusters of these cells throughout the different timepoints and thereby monitor changes in their gene expression profiles. We were able to compare our data to human studies (van Zyl et al, 2020;van Zyl et al, 2022) and found that human marker genes such as krt4, krt5 and myoc are expressed in the zebrafish cornea and AL respectively. Moreover, we found previously unknown markers like hgd and cndp1 expressed in the AL which might also play a role in human TM development (Vöcking and Famulski, 2023).…”
Section: Zebrafish Developmental Single Cell Transcriptome Applicatio...mentioning
confidence: 60%
“…Lo Faro et al (2021 identified an association between POAG and polymorphisms in the mitochondrial genes mt-Nd4 (rs2853496) and mt-Cyb (rs35788393). Atp2a1 encodes one of the Serca Ca (2+)-ATPases, which are intracellular pumps located in the sarcoplasmic or endoplasmic reticula of muscle cells (Odermatt et al, 1996), and Serca1 is also expressed in some non-muscle tissues, including the trabecular meshwork, which is a tissue in the eye that plays a role in regulating intraocular pressure (van Zyl et al, 2020). Thus, Atp2a1 potentially affects the regulation of intraocular pressure and contributes to the development of glaucoma.…”
Section: Discussionmentioning
confidence: 99%